Lighter Ingestion as an Uncommon Cause of Severe Vomiting in a Schizophrenia Patient - Yahya Atayan; Yasir Furkan Cagin; Mehmet Ali Erdogan; Yılmaz Bilgic; Remzi Bestas; Murat Harputluoglu; Yüksel Seckin (Case Reports in Gastrointestinal Medicine)
Background. Foreign bodies in the gastrointestinal tract are important morbid and mortal clinical conditions. Particularly, emergency treatment is required for cutting and drilling bodies. The majority of ingested foreign bodies (80–90%) leave gastrointestinal tract without creating problems. In 10–20% of cases, intervention is absolutely required. Less than 1% of cases need surgery. In this paper, we present a schizophrenia patient who swallowed multiple lighters. Case. A 21-year-old male schizophrenic patient who uses psychotic drugs presented to the emergency department with the complaints of abdominal pain, severe vomiting, and inability to swallow for a week. His physical examination revealed epigastric tenderness. A plain radiograph of the abdomen revealed multiple tiny metallic densities. Gastroscopy was performed. The lighters were not allowing the passage, and some of them had penetrated the gastric mucosa, and bezoars were observed. One lighter was extracted with the help of the polypectomy snare. Other lighters as a bezoar were removed by surgery. Conclusion. Excessive vomiting of swallowed foreign bodies in the etiology of psychotic patients should be kept in mind. Endoscopic therapy can be performed in the early stages in these patients, but in the late stage surgery is inevitable.